Social Resilience of the Baha'i Community During the Covid-19 Pandemic - Ashabul Kahfi, Muhammad; Jamaluddin, Fitriani; Bahtiar, Bahtiar; Ibrahim, Intan Soliha; Hasyim, Baso (LP2M IAIN Palopo, 2023)
This study aims to determine the condition of the Baha'i community in Palopo during the COVID-19 pandemic and the strategies practiced by the Baha'i community in Palopo to overcome the impact they felt during the COVID-19 pandemic. This research is qualitative research with an ethnographic approach. The research informants are the Baha'i community in Palopo City, the Ministry of Religion of Palopo City, the Population and Civil Registration Office of Palopo City, and the Palopo City Religious Communication Forum. Research data shows that the Baha'i community feels the impact of the pandemic in two aspects, namely (1) a decrease in income and employment and (2and ) psychological aspects in the form of stress due to physical distancing policies that limit interaction and congregational worship. For this impact, the Baha'i community uses several strategies, namely (1) family intimacy, (2) Social networks and trust relationships (3) technological adaptation and spiritual piety.